Quantitative approach to project portfolio management: proposal for Slovak companies - Kral, Pavol; Valjaskova, Viera; Janoskova, Katarina (Oeconomia Copernicana, 2019)
Research background: Project portfolio optimization isa demanding process in the case of considering a large number of project intentions and has so far been the subject of research by many authors, especially foreign authors. However, the issue of project portfolio optimization is an area that is not sufficiently addressed by Slovak authors. This was the main impulse to create a specific mathematical model of integer programming with bivalent variables to optimize the company's project portfolio with the intention to reflect the specific requirements of Slovak companies. Purpose of the article: The aim of the article is to propose a mathematical model of integer programming with bivalent variables to optimize the project portfolio with a focus on Slovak companies. Methods: In accordance with the aim of the article, a questionnaire survey was carried out with the intention of identifying the criteria that are perceived by the managers of Slovak companies as important in the optimization of the project portfolio. These criteria were subsequently reflected in the mathematical model design using the mathematical programming method. Findings Value added: Based on a literature review aimed at the project portfolio optimization, we have found a gap in considering the compliance of project intentions and strategic objectives of the company within the optimization of the project portfolio. Based on the results of the questionnaire survey, the significance of the mutual compliance of project intentions with the strategic objectives of the company was confirmed from the point of view of Slovak companies. Given the fact that our aim was to create an innovative integer programming model with bivalent variables orientated to the conditions of Slovak companies, we included in the resulting model the criteria that were not considered within the scope of existing research in this area, and which are perceived as important by the Slovak companies.